Hidden chaotic sets in a Hopfield neural system. (October 2017) - Danca, Marius-F.; Kuznetsov, Nikolay
Highlights: A Hopfield neural network is considered. Pair of hidden chaotic attractors and transients are identified. No hidden chaotic attractors found in this system. Abstract: In this paper we unveil the existence of hidden chaotic sets in a simplified Hopfield neural network with three neurons. It is shown that beside two stable cycles, the system presents hidden chaotic attractors and also hidden chaotic transients which, after a relatively long life-time, fall into regular motions along the stable cycles.